Cost-benefit analysis for the installation of cogeneration CSP technology in Cyprus - Poullikkas, Andreas (2013)
The purpose of this work is to investigate whether the installation of an innovative cogeneration of electricity and desalinated water (DSW) with concentrated solar power (CSP) technology in Cyprus is economically feasible. The study takes into account the following generating technologies, (a) CSP-DSW technology 4 MWe, (b) CSP-DSW technology 10 MWe, (c) CSP-DSW technology 25 MWe and (d) CSP-DSW technology 50 MWe with or without CO2 trading for two different cases of electricity purchasing tariff. For all above cases the electricity unit cost or benefit before tax, as well as internal rate of return (IRR) and payback period (PBP) are calculated. The results indicate that the electricity unit cost or benefit for both cases of electricity purchasing tariff are decreased or increased with the increase of the capacity factor and the capacity size of the plant. Also, the additional benefit due to the CO2 ETS price of 10 €/tCO2 for all scenarios is 0.8 €c/kWh. Specifically, for the electricity purchasing tariff of 26 €c/kWh case, the investment in CSP-DSW technology for every capacity size is very attractive, since, the CSP-DSW scenarios have high after tax IRR and low PBP. Despite the lower electricity unit cost benefit in the case of electricity purchasing tariff of 12.83 €c/kWh compared to that of the 26 €c/kWh case, which in some cases there is cost and not benefit, for CSP-DSW plants of 25 MWe and 50 MWe, the investment in this technology is still attractive.